2021
DOI: 10.3390/foods10030658
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of Whey:Casein Ratio from 20:80 to 60:40 in Milk Formulation Affects Food Intake and Brainstem and Hypothalamic Neuronal Activation and Gene Expression in Laboratory Mice

Abstract: Adjustment of protein content in milk formulations modifies protein and energy levels, ensures amino acid intake and affects satiety. The shift from the natural whey:casein ratio of ~20:80 in animal milk is oftentimes done to reflect the 60:40 ratio of human milk. Studies show that 20:80 versus 60:40 whey:casein milks differently affect glucose metabolism and hormone release; these data parallel animal model findings. It is unknown whether the adjustment from the 20:80 to 60:40 ratio affects appetite and brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Similarly, as the casein portion increased in milk protein from 20% to 100%, solid curd was easily formed in simulated gastric conditions ( Mulet-Cabero et al, 2020 ). Recently, Wood et al (2021) reported that modification of goat milk-based protein formulation from 80:20 to 40:60 influenced food intake and hypothalamic neuronal activation in mice. In addition, modification of the casein:whey protein (CW) ratio to 40:60 reduced the allergenic potential compared to natural cow’s milk ( Lara-Villoslada et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, as the casein portion increased in milk protein from 20% to 100%, solid curd was easily formed in simulated gastric conditions ( Mulet-Cabero et al, 2020 ). Recently, Wood et al (2021) reported that modification of goat milk-based protein formulation from 80:20 to 40:60 influenced food intake and hypothalamic neuronal activation in mice. In addition, modification of the casein:whey protein (CW) ratio to 40:60 reduced the allergenic potential compared to natural cow’s milk ( Lara-Villoslada et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the effect of whey:casein adjustment on single tastant intake bears some similarities between CM and (with what had been previously reported) GM [ 31 ], it cannot be directly compared. That is because the earlier report used shorter mealtimes and—in the post-deprivation feeding—utilized simultaneous presentation of GM and chow.…”
Section: Discussionmentioning
confidence: 98%
“…The composition of the prepared solutions can be found in Table 1 . In addition to CM formulations, in Experiment Section 2.3.4 , we used equivalent whey:casein ratio GM-based formulations that had been previously tested in laboratory animal feeding trials [ 31 ]. All formula compositions follow Codex standard (CODEX STAN 72-1981; based on nutrients/energy value), which requires lactose to be within the range of 5.4–9.8 g/100 mL.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations